2019
DOI: 10.1016/j.eclinm.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding self-harm in older adults: A qualitative study

Abstract: Background Self-harm is the leading risk factor for suicide, with elevated rates reported amongst older populations. This study explores how older adults experience self-harm, identifying factors leading to self-harm. Methods Semi-structured interviews with older adults (≥ 60 years) engaging in self-harm and support workers from third sector services in England. Older adults were invited to participate in a follow-up interview. Interviews were recorded, transcribed verb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…3,4 Furthermore, increased treatment costs exist when treating older adults who selfharm owing to complications caused by comorbidities. 5 The authors' previous work 6 suggests self-harm holds several functions for older adults and suicidal intent is not the only reason they engage in such behaviour, as traditionally reported. 4 Accounts of older adults using self-harm as a coping mechanism throughout the life course suggest the need for a more nuanced approach to intervening and providing support than one principally focused on suicide prevention.…”
Section: Introductionmentioning
confidence: 89%
“…3,4 Furthermore, increased treatment costs exist when treating older adults who selfharm owing to complications caused by comorbidities. 5 The authors' previous work 6 suggests self-harm holds several functions for older adults and suicidal intent is not the only reason they engage in such behaviour, as traditionally reported. 4 Accounts of older adults using self-harm as a coping mechanism throughout the life course suggest the need for a more nuanced approach to intervening and providing support than one principally focused on suicide prevention.…”
Section: Introductionmentioning
confidence: 89%
“…In terms of age, rates do seem higher among younger groups, and some studies suggest that most people who self-harm as teenagers stop by the time they are in their 30s [ 5 ]. However, studies also show that self-harm can begin in later life, or continue across the life course, and may be significantly under-reported among older groups [ 6 , 7 ]. Where studies engage with race (and often they do not), findings are varied—some studies in UK contexts find no evidence of patterns by ethnic group [ 3 ]; however, one study based in the Southern US found that the highest reported rates were among black males [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Liu et al's ( 45 ) review, a medium effect size was found for the relationship of CSA to non-suicidal self-injury. CSA was associated with an over 6-fold increase in repeated self-harm, with CSA being linked with loss and shame ( 46 ). Violent victimization is predictive of Indigenous boys' and girls' suicidal ideation and attempts ( 47 ), although CSA was not uniquely measured.…”
Section: Csa and Suicidalitymentioning
confidence: 99%